2013
DOI: 10.1186/1471-2180-13-216
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of infectious hepatitis A virus and rotavirus by combining dyes and surfactants with RT-qPCR

Abstract: BackgroundHuman enteric viruses are major agents of foodborne diseases. Because of the absence of a reliable cell culture method for most of the enteric viruses involved in outbreaks, real-time reverse transcriptase PCR is now widely used for the detection of RNA viruses in food samples. However this approach detects viral nucleic acids of both infectious and non infectious viruses, which limits the impact of conclusions with regard to public health concern. The aim of the study was to develop a method to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 40 publications
0
64
0
Order By: Relevance
“…Recently, the utility of viability RT-qPCR has been expanded by modifications to this basic strategy. Surfactant cotreatment was reported to facilitate PMA and EMA penetration in thermally inactivated HAV and rotavirus, thereby improving the ability to discern their viability (Coudray-Meunier et al, 2013). However, reports on the application of this methodology in environmental samples are somewhat limited.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, the utility of viability RT-qPCR has been expanded by modifications to this basic strategy. Surfactant cotreatment was reported to facilitate PMA and EMA penetration in thermally inactivated HAV and rotavirus, thereby improving the ability to discern their viability (Coudray-Meunier et al, 2013). However, reports on the application of this methodology in environmental samples are somewhat limited.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Coudray-Meunier et al (2013) found that treatments combining viability dyes and surfactants were effective for differentiating infectious and thermally inactivated HAV suspensions. The purpose of this work was then to assess the applicability of viability dyes for the detection and quantification of infectious HAV by RT-qPCR in lettuce wash water, as an example of the fresh-cut industry water, as well as in artificially inoculated foods including vegetables and shellfish.…”
Section: Introductionmentioning
confidence: 98%
“…Although coupling PMA with qPCR or RT-qPCR has been successfully applied to discriminate infectious and inactivated virus particles from viral suspension, river water, vegetables, swine raw manure, swine effluent from anaerobic biodigesters and biofertilized soil (Parshionikar et al, 2010; Sanchez et al, 2012; Coudray-Meunier et al, 2013; Moreno et al, 2015; Fongaro et al, 2016) little is known about the applicability of this technique in complex animal origin foods. In this study we chose two different food matrices: clam and Spanish fermented sausage (“chorizo”).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that EMA was less effective than PMA in selective amplification of DNA from viable cells and PMA was a useful alternative (van Frankenhuyzen et al, 2011). Besides viable cells of bacterial pathogens (Nocker and Camper, 2006, 2009; Nocker et al, 2007a; Pan and Breidt, 2007; Luo et al, 2010; Li and Chen, 2012, 2013), the PMA-qPCR has been applied to detect viable cells of fungi (Vesper et al, 2008), parasites (Brescia et al, 2009; Cancino-Faure et al, 2016), and viruses (Fittipaldi et al, 2010; Parshionikar et al, 2010; Kim and Ko, 2012; Sanchez et al, 2012; Coudray-Meunier et al, 2013; Fuster et al, 2016). …”
Section: Which Dye Work Better For Viability Detection Of Foodborne mentioning
confidence: 99%